Sick building syndrome: The effects of animal and plant-based adhesive in wood furniture (ARTEKS : Jurnal Teknik Arsitektur, 2023)
Sick building syndrome (SBS) is a condition that afflicts occupants of a building, typically a workplace, and is linked to time spent in the building(Thach et al., 2019). The precise cause for SBS is still unknown. However, there are a few possibilities that is believed to be the cause of SBS such as poor ventilation, bad lighting design, presence of mold, fungus and formaldehydes which is usually found in wood furniture. This research paper focuses on the furniture factor of SBS. Certain material and finishes used in furniture production are harmful to the users as it has the potential to emit chemical substances from the wood composite products(Jeon et al., 2011) which could affect the indoor air quality. Furniture production may not sound harmful, but if the processes were observed in detail, we can see animal exploitations along the progress. Adhesives used to join the furniture may have substances that are derived from animals. The objective of this research is to study the chemical component in an animal-based adhesive and plant-based adhesive in wood furniture that is commonly used in lobby or lounge area (sofa, coffee table, etc.). With the chemical components identified, it is used to see how it contributes to the Sick Building Syndrome and which adhesives will be a better option for furniture production. This research also aims to compare animal-based and plant-based adhesives in terms of quality and cost. This research uses the qualitative method in which we look at past research first-hand observations, interviews, data, etc. The outcome by the end of this research will achieve all research objectives and suggest a better adhesive in wood furniture production whether it is animal-based or plant-based adhesives that has the least effect to SBS. This research can be beneficial to all furniture companies that are finding an alternative for a safer and greener choice of adhesive in wood furniture production. This research can also be a guideline to help improve the quality in furniture production and reduce the risk of SBS.
Keywords: Adhesives; Animal; Plant; Sick building syndrome; Wood furniture